ANALISIS POTENSI PEMBANGKIT LISTRIK TENAGA OTEC (OCEAN THERMAL ENERGI CONVERSION) WILAYAH KALIANGET DONAN CILACAP - Andi Hendrawan (Sekolah Tinggi Maritim Yogyakarta, 2017)
Oceans cover 71 percent of the earth’s surface. They constitute a natural solar energy collection and storage system, and the resulting thermal energy can be drown off 24 hours a day by OTEC Plant. OTEC (ocean thermal energy conversion) power plant is one candidate to produce electric energy. OTEC transforms the heat stored in surface water of tropical oceans into mechanical work to produce useful energy. The aim of this paper was to investigate the equation of boiler in OTEC technology. The surface temperature of the sea water which is located Kalianget donan and Cilacap region between 32 up to 35 with a depth of 30 to 100 meters produce the greatest efficiency is 0.19.